Development of a health literacy assessment for young adult college students: a pilot study - Arif Shah, Jasmin; Hamzah, Siti Raba’ah; Suandi, Turiman; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2017)
Several conceptual models have been developed to measure health literacy. However, health literacy of the community, particularly the young is still under reported and under-explored. The purpose of this study was to develop and validate health literacy assessment tool for high school students. Participants were 150 students. The concept of health literacy evolved from defining, redefining, outlining and quantifying health literacy needs of a young population. Seven health education experts reviewed the initial item pool and helped select 85 questions for testing. The reviewer also provided confidential feedback via an evaluation questionnaire. Seven distinct health literacy domains meanings emerged viz health promotion, health care, disease prevention, health behaviour, health attitude, health wellbeing and health culture. The instrument has 85 questions that look promising for measuring health literacy in high school students, but needs additional and continuous testing with larger population to see how these questions continue to perform. The findings of present study might be a useful policy maker and health organizations to reflect and focus their promotion efforts on the more practical aspects of day-to-day in health promotion and are concerned with empowering young through enhancing their knowledge and improving their ability to make choices about their health well-being.